Soundscape structure in forests surrounded by protected and productive areas in central Costa Rica - Retamosa Izaguirre, Mónica; Barrantes Madrigal, Jimy (Frontiers in Remote Sensing, 2023)
Ecosystems are under a multitude of pressures, including land-use change, overexploitation, pollution, and climate change. Most studies, resources, and conservation efforts are allocated to protected areas, while anthropogenic activities in their surroundings may affect them in ways that are poorly understood. We evaluated soundscape structure in forests surrounded by protected or productive areas in central Costa Rica. We sampled soundscapes in 91 recording sites in Grecia Forest Reserve and Poas Volcano National Park, and surrounding areas with productive activities (predominantly agricultural and urban). We classified sampling sites into three clusters according to landscape entropy, forest amount, and fragmentation surrounding recording points: more fragmented, more conserved, and intermediate. The conserved cluster showed higher acoustic diversity or entropy, but lower acoustic complexity, shorter duration of sounds in all frequency ranges, and lower amount of energy in the biological frequency bands than the fragmented cluster. We additionally found a positive significant relationship between the amount of forest and acoustic entropy or diversity indices, but a negative relationship with acoustic activity or energy indices. Indices, such as spectral and temporal entropy, the entropy of spectral variance, and total entropy, seemed to be a better fit than acoustic complexity and bioacoustic indices as indicators of habitat conservation in this study. Acoustic indices revealed that the surrounding matrices of protected areas have an impact on acoustic environments. We encourage researchers and decision-makers to carefully interpret acoustic indices when evaluating habitats showing a higher value in acoustic energy or activity because this might not necessarily reflect either a high level of biodiversity or habitat conservation. Also, we highlight the importance of preserving undisturbed forested matrices around protected areas, as they are important for maintaining acoustic diversity.